2015
DOI: 10.1186/s12866-015-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota characterisation of horses using 16 rdna barcoded pyrosequencing, and carriage rate of clostridium difficile at hospital admission

Abstract: BackgroundThe equine faecal microbiota is very complex and remains largely unknown, while interspecies interactions have an important contribution to animal health. Clostridium difficile has been identified as an important cause of diarrhoea in horses. This study provides further information on the nature of the bacterial communities present in horses developing an episode of diarrhoea. The prevalence of C. difficile in hospitalised horses at the time of admission is also reported.ResultsBacterial diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 53 publications
8
81
0
1
Order By: Relevance
“…It has been recently introduced to investigate the intestinal microbiota of healthy patients and patients suffering CDI. In the last year, most of the studies reported bacteria at the phylum and class level, but higher taxonomic resolution may reveal more differences in the population structure [206]. Preliminary results have shown that one of the taxa found in high proportions in patients with CDI is Proteobacteria, while Bacteroidetes proportions are lower in infected patients [207].…”
Section: High-throughput Sequencing Analysis and CDImentioning
confidence: 92%
“…It has been recently introduced to investigate the intestinal microbiota of healthy patients and patients suffering CDI. In the last year, most of the studies reported bacteria at the phylum and class level, but higher taxonomic resolution may reveal more differences in the population structure [206]. Preliminary results have shown that one of the taxa found in high proportions in patients with CDI is Proteobacteria, while Bacteroidetes proportions are lower in infected patients [207].…”
Section: High-throughput Sequencing Analysis and CDImentioning
confidence: 92%
“…Sequence read processing for 16S and 26S was used as previously described using MOTHUR software package v1.35 (Schloss et al 2009), Pyronoise algorithm and UCHIME algorithm (Edgar et al 2011) for alignment and clustering, denoising and chimera detection, respectively (Rodriguez et al 2015;Degrune et al 2016). Amplicon reference alignment and taxonomical assignation were based upon the SILVA database (v1.15) of full-length SSU (16S) and LSU (26S) rDNA sequences (Quast et al 2012).…”
Section: Bioinformatic Analyses Of Metabarcoding Datamentioning
confidence: 99%
“…Sequence reads processing were used as previously described by Rodriguez et al (2015) using respectively MOTHUR software package v1.35, Pyronoise algorithm and UCHIME algorithm for alignment and clustering, denoising and chimera detection. The clustering distance for operational taxonomic unit (OTU) is 0.03.…”
Section: Bioinformatics Analysismentioning
confidence: 99%